Cupper Acetyl Acetone Catalyzed Synthesis of 1, 3, 5-Triaryl-2-Pyrazolines Derivatives from Chalcone - Santosh V. Padghan (International Journal of Scientific Research in Chemistry, 2025)
Heterocyclic compounds represents an important class of biologically active molecules specifically, those containing the pyrazolone nucleus have been shown to posses high biological activities such as tranquillizing, muscle relaxant, psycho analeptic, anticonvulsant, antihypertensive, antidepressant activities. Despite their potential utility, some of the methods described have disadvantages such as long reaction times, time-consuming product, isolation procedures and environmental problems. In this method, we have reported the synthesis of pyrazoline derivatives using series of substituted chalcones by condensation with phenyl hydrazine and copper acetyl acetonate as a catalyst using ethanol as solvent.